LEXICOGRAPHICAL APPROACH: DIFFERENCES IN RENDERING THE MEANINGS OF “SADOQAT” AND “LOYALTY” IN UZBEK AND ENGLISH DICTIONARIES - Khamrayeva Charos Norboyevna (Western European Studies, 2025)
The Uzbek term sadoqat and its English equivalent, loyalty, are compared lexicographically in this study using Uzbek Wiktionary, Oʻzbek tilining izohli lugʻati, and Oxford Learner's Dictionary. The study delineates semantic and cultural divergences, structuring its inquiry across definitions, a comparative table, and implications, revealing that sadoqat emphasizes emotional-ethical commitment rooted in Arabic origins and collectivist values, while loyalty extends to pragmatic domains like commerce and politics and establishes the purpose: to uncover nuanced differences in conceptual expression between the languages. Tasks include obtaining dictionary definitions and actual discourse, with technique incorporating comparative linguistics, semantic field theory, and corpus analysis from materials including the British National Corpus, media texts, political speeches, and literary works.
Keywords: lexicography; sadoqat; loyalty; Uzbek dictionaries